Human herpesvirus 8 (HHV-8) detected by nested polymerase chain reaction (PCR) in HIV patients with or without Kaposi’s sarcoma. An analytic cross-sectional study - Machado, Paula Renata Lima; Farias, Kleber Juvenal Silva; Pereira, Maira Gabriela Martins; Freitas, Patrícia Pereira da Silva de; Fonseca, Benedito Antônio Lopes da (São Paulo Medical Journal, 2016)
CONTEXT AND OBJECTIVE: Kaposi’s sarcoma (KS) is a common neoplastic disease in AIDS patients. The aim of this study was to evaluate the frequency of human herpesvirus 8 (HHV-8) infection in human immunodeficiency virus (HIV)-infected patients, with or without KS manifestations and correlate HHV-8 detection with KS staging. DESIGN AND SETTING: Analytic cross-sectional study conducted in a public tertiary-level university hospital in Ribeirão Preto, São Paulo, Brazil. METHODS: Antibodies against HHV-8 lytic-phase antigens were detected by means of the immunofluorescence assay. HHV-8 DNA was detected in the patient samples through a nested polymerase chain reaction (nested PCR) that amplified a region of open reading frame (ORF)-26 of HHV-8. RESULTS: Anti-HHV-8 antibodies were detected in 30% of non-KS patients and 100% of patients with KS. Furthermore, the HHV-8 DNA detection rates observed in HIV-positive patients with KS were 42.8% in serum, 95.4% in blood samples and 100% in skin biopsies; and in patients without KS, the detection rate was 4% in serum. Out of the 16 serum samples from patients with KS-AIDS who were classified as stage II, two were positive (12.5%); and out of the 33 samples from patients in stage IV, 19 (57.6%) were positive. CONCLUSION: We observed an association between HHV-8 detection and disease staging, which was higher in the serum of patients in stage IV. This suggests that detection of HHV-8 DNA in serum could be very useful for clinical assessment of patients with KS and for monitoring disease progression.